Implementasi Kebijakan Pemerintah dalam Pengembangan Program Pembiayaan UMKM di Kota Palembang - Namira, Balqis; Azhar, Azhar; Permatasari, Indah (Mahesa Research Center, 2024)
This study aims to examine the implementation of government policies in developing Micro, Small, and Medium Enterprises (MSMEs) in Palembang City. The research employs a qualitative descriptive method, with data collected through observations, interviews, and documentation. The participants in this study include MSME practitioners, government officials, and other relevant stakeholders. The findings reveal that the Palembang City Government has implemented policies and provided various facilities and stimuli to support MSMEs. However, there are still deficiencies in the support provided, such as the procurement of production tools and other physical goods. Additionally, adequate, appropriate, and practical methods, mechanisms, and procedures are required to enhance MSME development. The main challenge in MSME development is the limited outreach to business practitioners and the general public's lack of understanding of government regulations and policies. The study concludes that to accelerate MSME development, improvements in outreach and strengthening public understanding of existing government policies are necessary.